RESPON ORANGTUA SISWA PENYANDANG AUTIS TERHADAP PELAYANAN PENDIDIKAN DI SEKOLAH ALAM MEDAN - Brian Melkisedek Ginting (Welfare StatE, 2013)
To see the baby under five years old growing and developing is one of the things that interesting for the parents. However, if the child has a development period of disruption, then parents will be very sad. One of the disorders in childhood who became frightened parent is autism. Current cases of autism in children, causing more and more concern among the public, especially parents, in addition to the negative stigma of society towards children with autism, parents are also faced with the problem of education of children with autism because children with autism do not have the ability to learn like normal children so that children with autism need special schools who deal with children with autism. This research is descriptive research that makes the overall picture of how the response of parents of students with autism. The research was conducted at the Sekolah Alam Medan is located at Jalan Bunga Wijaya Kusuma no. 23, Pasar 4, Padang Bulan, Medan, the number of those 30 people. Techniques of data collection through questionnaires, observations and interviews directly to the respondents. Respondents were then given a questionnaire respondents are presented in tabular form and then conducted a quantitative analysis of the Likert scale. Based on the data that has been collected and analyzed, it can be concluded that the response of parents of students with autism to the services at the School of Natural Terrain education is positive with a value of 0.95. Consists of perceptions and attitudes to the value of 0.99 with a value of 0.93 and 0.93 to the value of participation. Parents expect educational services for children with autism can be improved for the better again. Keywords: parental response, ministry of education of children with autism Keywords: parentalresponse, ministryof educationof children with autism and Sekolah Alam Medan